2016
DOI: 10.1371/journal.pone.0154728
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Contrast: Yellow Flower Colour Constrains Style Length in Crocus species

Abstract: Most flowers display distinct colour patterns comprising two different areas. The peripheral large-area component of floral colour patterns attracts flower visitors from some distance and the central small-area component guides flower visitors towards landing sites. Whereas the peripheral colour is largely variable among species, the central colour, produced mostly by anthers and pollen or pollen mimicking floral guides, is predominantly yellow and UV-absorbing. This holds also for yellow flowers that regularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In a similar way, wild-type flowers of Antirrhinum majus appear blue to bumblebees, and are both preferred and processed faster than genetically modified mutant flowers of bee-white appearance ( Dyer et al, 2007 ). Nevertheless, it has also to be considered that many flowers are multi-colored, and the effects of such color patterning on pollinators and their preferences for different parts of the spectrum are complex and only starting to be explored ( Lunau et al, 2016 ). In Germany, it was reported that blue flowers more frequently presented higher reward ( Giurfa et al, 1995 ) than alternative flower colors.…”
Section: Plant–pollinator Interactionsmentioning
confidence: 99%
“…In a similar way, wild-type flowers of Antirrhinum majus appear blue to bumblebees, and are both preferred and processed faster than genetically modified mutant flowers of bee-white appearance ( Dyer et al, 2007 ). Nevertheless, it has also to be considered that many flowers are multi-colored, and the effects of such color patterning on pollinators and their preferences for different parts of the spectrum are complex and only starting to be explored ( Lunau et al, 2016 ). In Germany, it was reported that blue flowers more frequently presented higher reward ( Giurfa et al, 1995 ) than alternative flower colors.…”
Section: Plant–pollinator Interactionsmentioning
confidence: 99%
“…(Peter and Johnson 2013), and Phaius delavayi (Li et al 2010). Imitations can also be found in the Scrophulariaceae Craterostigma plantaginea and Torenia polygonoides (Magin et al 1989), diclinous begonias (Å gren and Schemske 1991;Schemske et al 1996;Wyatt and Sazima 2011;Castillo et al 2012), and Crocus flowers with stamen-imitating styles (Lunau et al 2016). Additionally, there is an abundance of flowers with conspicuous staminodes (Hardy and Stevenson 2000;Hrycan and Davis 2005;Ushimaru et al 2007;Walker-Larsen and Harder 2000) and various types of imitations in other flowering plants (Bernhardt et al 1984;Simpson et al 1986;Weber 1989;Harder and Barclay 1994;Leins and Erbar 1994;Barthlott 1995;Dobson et al 1996;Peisl 1997;Lunau 2000Lunau , 2007Sigrist and Sazima 2004;Sá-Otero et al 2009).…”
Section: And Klaus Lunaumentioning
confidence: 99%
“…Crocus species (Lunau et al 2016). A common type of colour pattern in all-yellow flowers is the combination of an orange floral guide with a yellow periphery without any UVpattern like in the California Poppy Eschscholzia californica (Papaveraceae) and Common Toadflax Linaria vulgaris (Plantaginaceae).…”
Section: Discussionmentioning
confidence: 99%